Table of Content - - (Journal of Curriculum and Teaching Methodology, 2024)
Table of Content: 1. The constrains of using the technologies of the augmented reality in teaching English from the point of view of the teaching staff at the colleges of languages and translation of Najran University Mrs. Amal Hamad Rashid Al Hudaisan 2. Attitudes of Teaching stuff and administrators at Saudi electronic university towards electronic tests and the extent to which they apply universal design standards UDL, difficulties and suggestions Mrs. Meaad Mohammed Dardeer, Mrs. Nayfa Abdullah Al-Ahmari, Dr. Hawazen Al-Harbi 3. The reality of the use of electronic blogging in the educational process from the point of view of teachers during psychological and social studies for the secondary stage in Makkah Mrs. Shroog Salem Al-Zahrani 4. The Role of a Design-Thinking-Based Instructional Strategy in Promoting 21st Century Skills Dr. Naif Ali Al-Amry, Prof. Rashid Hussein Al-Abdul Al-Karim